Evolving role of clinical pharmacist in the management of diabetes mellitus - Shareef, Javedh; Fernandes, Jennifer; Samaga, Laxminarayana (International Journal of Research in Medical Sciences, 2017)
Diabetes mellitus is a metabolic disorder characterised by hyperglycaemia due to impaired insulin secretion with or without insulin resistance. Uncontrolled blood glucose in the long term will lead to micro vascular and macro vascular complications with increased morbidity and mortality and negatively affecting the quality of life. Comprehensive diabetes care is a complex task that takes the entire team of healthcare professionals including the pharmacist to work together to provide, multidisciplinary care for patients. Pharmacist’s role has changed dramatically over the past three decades which has changed the concept of pharmacy from product oriented to a patient focused one with the concept of pharmaceutical care. The evolving role of clinical pharmacist in the management of diabetes mellitus - drug therapy, diabetes care and education has been described here. Optimizing the drug therapy for achieving the better therapeutic outcomes without causing drug related problems has been considered as the primary goal of therapy in the diabetes management. Well trained and readily accessible clinical pharmacists are the key healthcare professionals who can move closer towards achieving better medication therapy outcomes for the patients. Clinical pharmacist coordinates with the physician during drug therapy and applies his clinical expertise in identifying, resolving and preventing drug related problems by providing interventions which is of valuable aid in accurate, safe and cost effective use of drugs for the physicians. In addition, pharmacist also plays a very important role on diabetes care and education by screening patients at high risk for diabetes, monitoring diabetic treatment goals, assessing patient’s health status and providing counseling for medication adherence which will help in optimizing the blood sugar level and enhancing the quality of life in patients with diabetes mellitus.